2020
DOI: 10.3390/d12020070
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Reconstruction Sheds Light on New Relationships and Timescale of Rails (Aves: Rallidae) Evolution

Abstract: The integration of state-of-the-art molecular techniques and analyses, together with a broad taxonomic sampling, can provide new insights into bird interrelationships and divergence. Despite their evolutionary significance, the relationships among several rail lineages remain unresolved as does the general timescale of rail evolution. Here, we disentangle the deep phylogenetic structure of rails using anchored phylogenomics. We analysed a set of 393 loci from 63 species, representing approximately 40% of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 59 publications
10
32
2
Order By: Relevance
“…We found that the endemic Galápagos Rail forms a monophyletic group indicative of a single colonization event to the Galápagos Islands around 1.2 Mya, with negligible differences depending on whether the Belgirallus fossil was considered a crown or stem rallid for the calibration of the dated tree (Table 1), an overall pattern contrasting the findings of García et al [50]. In comparison with other Galápagos land bird colonizers, rails coincide with the estimated arrival of Darwin’s finches (1.5–1.0 Mya [57,58] and flycatchers (genus Pyrocephalus : 1 Mya [59]; Myiarchus : 850 kya [60]).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that the endemic Galápagos Rail forms a monophyletic group indicative of a single colonization event to the Galápagos Islands around 1.2 Mya, with negligible differences depending on whether the Belgirallus fossil was considered a crown or stem rallid for the calibration of the dated tree (Table 1), an overall pattern contrasting the findings of García et al [50]. In comparison with other Galápagos land bird colonizers, rails coincide with the estimated arrival of Darwin’s finches (1.5–1.0 Mya [57,58] and flycatchers (genus Pyrocephalus : 1 Mya [59]; Myiarchus : 850 kya [60]).…”
Section: Discussioncontrasting
confidence: 99%
“…We used the fossil data compiled in Stervander et al [47], setting a prior for Rallidae following a lognormal distribution with mean 1.1, standard deviation 1.8, and offset 32.6 million years. However, as rightly pointed out by Garcia et al [50], the inclusion of Belgirallus to calibrate crown Rallidae may not be correct, as Belgirallus may rather be representative of a stem rallid species [51]. We therefore primarily applied this prior to date stem Rallidae (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The finfoots/sungrebe (Heliornithidae), adzebills (Aptornithidae), flufftails (Sarothruridae) and Nesotrochis clade contains many species that are morphologically convergent with rallids, with which they shared a common ancestor likely during the early Cenozoic [11,27]. Holocene extinctions have greatly diminished this clade; combined data from morphology and aDNA indicate 50% family level extinction during the Holocene (herein; [11]).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genome of Rallicula forbesi ( Rallina per [26]) was obtained by mapping the raw read data from Garcia-R et al . [27] to the mitochondrial genome of C. oculeus in Geneious (v. 11.1.4) using the Medium-Low Sensitivity default settings. Along with extant species, we included partial mitochondrial genomes of the extinct New Zealand adzebills: A. otidiformis and Aptornis defossor (Aptornithidae; [11]).…”
Section: Methodsmentioning
confidence: 99%
“…We compiled a database for all 144 species of extant rails (including 42 island endemic species) using the 2019 version of the International Union for Conservation of Nature (IUCN) Red List (IUCN, 2019) and the 'Guide to the Rails, Crakes, Gallinules and Coots of the world' (Taylor & van Perlo, 1998). We used the taxonomic classification followed by the IUCN which included the rallid family of Sarothruridae (some authors consider it separate from the Rallidae family, see Garcia-R. et al, 2014;Garcia-R et al, 2020). The Sarothruridae family contains 15 species, including two threatened species, and is mostly present in the Afrotropics.…”
Section: Database Compilationmentioning
confidence: 99%